From simple questions to complex issues, IDNLearn.com has the answers you need. Get prompt and accurate answers to your questions from our experts who are always ready to help.
Sagot :
To determine which formula is correct based on the relationship [tex]\( v = c \lambda \)[/tex], let's analyze each option.
1. [tex]\( v = c \lambda \)[/tex]:
- This is the original equation provided. Clearly, this should be correct.
2. [tex]\( v \div \lambda = c \)[/tex]:
- We can rearrange the original equation [tex]\( v = c \lambda \)[/tex] to solve for [tex]\( c \)[/tex]:
[tex]\[ v = c \lambda \implies \frac{v}{\lambda} = c \][/tex]
- This indicates that this formula is also correct.
3. [tex]\( v + \lambda = c \)[/tex]:
- According to the original equation [tex]\( v = c \lambda \)[/tex], if we add [tex]\( \lambda \)[/tex] to [tex]\( v \)[/tex], it doesn't directly relate to [tex]\( c \)[/tex]. Therefore, this formula is incorrect.
4. [tex]\( v \lambda = c \)[/tex]:
- If we multiply [tex]\( v \)[/tex] by [tex]\( \lambda \)[/tex], we obtain a term that does not match the original equation [tex]\( v = c \lambda \)[/tex]. Therefore, this formula is incorrect.
5. [tex]\( \lambda = c v \)[/tex]:
- Rearranging the original equation [tex]\( v = c \lambda \)[/tex] to solve for [tex]\( \lambda \)[/tex] gives:
[tex]\[ \lambda = \frac{v}{c} \][/tex]
- The formula [tex]\( \lambda = c v \)[/tex] does not match this rearrangement, so it is incorrect.
So, the correct formulas based on the equation [tex]\( v = c \lambda \)[/tex] are:
1. [tex]\( v = c \lambda \)[/tex]
2. [tex]\( v \div \lambda = c \)[/tex]
Thus, the correct formulas are the first and the second ones as they are the only ones consistent with [tex]\( v = c \lambda \)[/tex]. The others are incorrect.
1. [tex]\( v = c \lambda \)[/tex]:
- This is the original equation provided. Clearly, this should be correct.
2. [tex]\( v \div \lambda = c \)[/tex]:
- We can rearrange the original equation [tex]\( v = c \lambda \)[/tex] to solve for [tex]\( c \)[/tex]:
[tex]\[ v = c \lambda \implies \frac{v}{\lambda} = c \][/tex]
- This indicates that this formula is also correct.
3. [tex]\( v + \lambda = c \)[/tex]:
- According to the original equation [tex]\( v = c \lambda \)[/tex], if we add [tex]\( \lambda \)[/tex] to [tex]\( v \)[/tex], it doesn't directly relate to [tex]\( c \)[/tex]. Therefore, this formula is incorrect.
4. [tex]\( v \lambda = c \)[/tex]:
- If we multiply [tex]\( v \)[/tex] by [tex]\( \lambda \)[/tex], we obtain a term that does not match the original equation [tex]\( v = c \lambda \)[/tex]. Therefore, this formula is incorrect.
5. [tex]\( \lambda = c v \)[/tex]:
- Rearranging the original equation [tex]\( v = c \lambda \)[/tex] to solve for [tex]\( \lambda \)[/tex] gives:
[tex]\[ \lambda = \frac{v}{c} \][/tex]
- The formula [tex]\( \lambda = c v \)[/tex] does not match this rearrangement, so it is incorrect.
So, the correct formulas based on the equation [tex]\( v = c \lambda \)[/tex] are:
1. [tex]\( v = c \lambda \)[/tex]
2. [tex]\( v \div \lambda = c \)[/tex]
Thus, the correct formulas are the first and the second ones as they are the only ones consistent with [tex]\( v = c \lambda \)[/tex]. The others are incorrect.
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. IDNLearn.com is committed to providing accurate answers. Thanks for stopping by, and see you next time for more solutions.